A Climate Index Optimized for Longshore Sediment Transport Reveals Interannual and Multidecadal Littoral Cell Rotations. Issue 8 (25th August 2018) - Anderson, Dylan; Ruggiero, Peter; Antolínez, José A. A.; Méndez, Fernando J.; Allan, Jonathan
Abstract: A recent 35‐year endpoint shoreline change analysis revealed significant counterclockwise rotations occurring in north‐central Oregon, USA, littoral cells that extend 10s of kilometers in length. While the potential for severe El Niños to contribute to littoral cell rotations at seasonal to interannual scale was previously recognized, the dynamics resulting in persistent (multidecadal) rotation were unknown, largely due to a lack of historical wave conditions extending back multiple decades and the difficulty of separating the timescales of shoreline variability in a high energy region. This study addresses this question by (1) developing a statistical downscaling framework to characterize wave conditions relevant for longshore sediment transport during data‐poor decades and (2) applying a one‐line shoreline change model to quantitatively assess the potential for such large embayed beaches to rotate. A climate IN dex was optimized to capture variability in longshore wave power as a proxy for potential LO ngshore S ediment T ransport (LOST_IN), and a procedure was developed to simulate many realizations of potential wave conditions from the index. Waves were transformed dynamically with Simulating Waves Nearshore to the nearshore as inputs to a one‐line model that revealed shoreline rotations of embayed beaches at multiple time and spatial scales not previously discernible from infrequent observations. Model results indicate that littoral cells respond to both interannual and multidecadal oscillations, producing comparable shoreline excursions to extreme El Niño winters. The technique quantitatively relates morphodynamic forcing to specific climate patterns and has the potential to better identify and quantify coastal variability on timescales relevant to a changing climate. Plain Language Summary: The global climate forces large atmospheric weather patterns which in turn create the ocean waves ultimately responsible for erosion at the coastline. As the global climate changes, so too can long‐term trends in coastal erosion. We have developed a technique to directly relate weather patterns to coastal change resulting from the transport of sediment along beaches and applied the method to investigate shoreline change trends in Oregon, USA, from the 1950s to the present. Counter to previous understanding, climate change on the timescale of multiple decades is responsible for which municipalities in Oregon experience persistent erosion hazards. The technique revealed the importance of large‐scale climate in changing storm tracks approaching Oregon across the North Pacific. The technique developed for identifying climate patterns relevant to local coastal dynamics could be a useful predictive tool for understanding how the coast may evolve on timescales relevant for coastal managers into the 21st century. Key Points: A framework is proposed to identify the magnitude and direction of longshore sediment transport from patterns of atmospheric variability One‐line shoreline change simulations reveal previously unquantified timescales of coastal change Interannual and multidecadal wave climate variability dominates long‐term evolution of headland‐bound littoral cells in Oregon